Using English to teach English: Classroom English competence of English language teachers in Vietnam - Hai Ha, Vu (VNU Journal of Science: Education Research, 2017)
The National Foreign Language Project 2020 (Project 2020) has been laying its emphasis on the development of general English language proficiency and English language teaching methods of English language teachers in Vietnamese schools. This article argues that these focuses might overlook an area which is essential for these teachers to use English efficiently in the classrooms: the development of classroom English proficiency. This argument is corroborated by a case study with qualitative data collected from videotaping 113 teachers in their microteaching sessions. It reveals certain limitations in their classroom English competence, especially linguistic and strategic competence. The article concludes by putting forward certain suggestions for Project 2020 as well as future studies to explore other facets of this competence.